2013
DOI: 10.1371/journal.pone.0073101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Neurolytic Celiac Plexus Block on Liver Regeneration in Rats with Partial Hepatectomy

Abstract: Liver regeneration is the basic physiological process after partial hepatectomy (PH), and is important for the functional rehabilitation of the liver after acute hepatic injury. This study was designed to explore the effects of neurolytic celiac plexus block (NCPB) on liver regeneration after PH. We established a model of PH in rats, assessing hepatic blood flow, liver function, and serum CRP, TNF-α, IL-1β and IL-6 concentrations of the residuary liver after PH. Additionally, histopathological studies, immunoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…The current study successfully established the model by using ANIT, and demonstrated that HOL could decrease liver index and degree of liver injury in the experimental model mice, indicating that HOL possesses potential hepatoprotective effects. Elevated SGPT and SGOT are two characteristic markers for hepatic injury [2,13,14]. In this study, the levels of SGPT and SGOT were sharply increased after ANIT treatment.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…The current study successfully established the model by using ANIT, and demonstrated that HOL could decrease liver index and degree of liver injury in the experimental model mice, indicating that HOL possesses potential hepatoprotective effects. Elevated SGPT and SGOT are two characteristic markers for hepatic injury [2,13,14]. In this study, the levels of SGPT and SGOT were sharply increased after ANIT treatment.…”
Section: Discussionsupporting
confidence: 48%
“…It is well known that the liver is a vital intraabdominal organ which performs important biological functions such as bile secretion, synthesis of plasma proteins and lipid biosynthesis [1,2]. It is known that liver injury may arise from excessive alcohol intake, as well as exposure to various toxins and environmental pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…Rats received 0.5% lidocaine (2 ml once/day) or saline under ether anesthesia. The puncture point was determined in accordance with a previous report (18). Briefly, rats were injected bilaterally at the first lumbar transverse process, the first bony protrusion under the root of the last rib.…”
Section: Gk Rat Model Of Niddmmentioning
confidence: 99%
“…Serum and quadriceps muscle samples for biochemical analyses were collected, which were stored at -80˚C until use. A 100 mg sample of freshly isolated soleus muscle was used to determine skeletal muscle 2-deoxy-D-glucose (2-DG) uptake in each rat (14). Soleus muscle bundles were placed in Krebs-Ringer bicarbonate buffer (OriGene Technologies, Inc., Beijing, China) with or without 1.0 µmol/ml insulin to measure insulin-stimulated and basal glucose uptake, respectively.…”
Section: Gk Rat Model Of Niddmmentioning
confidence: 99%
See 1 more Smart Citation